Orthodontic retreatment using anchorage with miniplate to camouflage a Class III skeletal pattern - Marcel Marchiori Farret (Dental Press Journal of Orthodontics)
ABSTRACT This manuscript describes the treatment of a 27-year-old patient who was previously treated with two maxillary first premolar extractions. The patient had skeletal Class III malocclusion, Class III canine relationship, anterior crossbite, and a concave profile. As the patient refused orthognathic surgery, a miniplate was used on the right side of the lower arch as an anchorage unit after the extraction of mandibular first premolars, aiding the retraction of anterior teeth. At the end of treatment, anterior crossbite was corrected, in which first molars and canines were in a Class I relationship, and an excellent intercuspation was reached. Furthermore, patient's profile remarkably improved as a result of mandibular incisor retraction. A 30-month follow-up showed good stability of the results obtained. This case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as one of the requirements to become diplomate by the BBO.